Genome‐wide association studies reveal additional related loci for fatty acid composition in a Duroc pig multigenerational population. (12th April 2017) - Sato, Shuji; Uemoto, Yoshinobu; Kikuchi, Takashi; Egawa, Sachiko; Kohira, Kimiko; Saito, Tomomi; Sakuma, Hironori; Miyashita, Satoshi; Arata, Shinji; Suzuki, Keiichi
Abstract: The aim of the present study was to detect quantitative trait loci affecting fatty acid composition in back fat and intramuscular fat in a Duroc pig population comprising seventh‐generation pedigrees using genome‐wide association studies (GWAS). In total, 305 animals were genotyped using single nucleotide polymorphisms (SNPs) array and five selected SNPs from regions containing known candidate genes related to fatty acid synthesis or metabolism. In total, 24 genome‐wide significant SNP regions were detected in 12 traits, and 76 genome‐wide suggestive SNP regions were detected in 33 traits. The Sus scrofa chromosome (SSC) 7 at 10.3 Mb was significantly associated with C17:0 in intramuscular fat, while the SSC9 at 13.6 Mb was significantly associated with C14:0 in intramuscular fat. The SSC12 at 1.0 Mb was significantly associated with C14:0 in back fat and the SSC14 at 121.0 Mb was significantly associated with C18:0 in intramuscular fat. These regions not only replicated previously reported loci containing some candidate genes involved in fatty acid composition ( fatty acid synthase and stearoyl‐CoA desaturase ) but also included several additional related loci.